Dynamic analysis of lead stocks and flows in China from 1990 to 2015. (20th December 2018) - Liu, Wei; Cui, Zhaojie; Tian, Jinping; Chen, Lujun
Abstract: Lead is the only toxic metal still in heavy use, and it is used in lead-acid batteries, alloys, and compounds in glass and plastics. This study illustrates the evolution of lead metabolism in China from 1990 to 2015 by applying substance flow analysis (SFA). Lead production and consumption in China increased by 11% and 12% per year in China, respectively. Lead in-use stocks increased from 0.78 to 12.2 Mt, and lead in-use stocks per capita increased from 0.69 to 8.86 kg/capita. Meanwhile, China experienced a rapid growth in lead losses with the explosion of lead metabolism. More than 94% of lead losses were leaded wastes such as dissipated leaded products, waste ores, tailings, and smelting slags. In addition, lead stocks in lead scraps also reached 3.6 Mt. The current lead in-use stocks and lead scraps can provide a huge amount of lead resources for China in the future. However, the rise of new battery technologies and the generalization of lead-free action are denting demand for lead. China should shift lead supplies from primary lead to secondary lead and strictly control lead pollution within the life-cycle of lead resources. Graphical abstract: Highlights: We analyzed lead stocks and flows in China from 1990 to 2015. Lead losses peaked at 1.89 Mt/yr in 2011, and more than 94% of them were leaded wastes. Lead in-use stocks in China increased from 0.78 to 12.2 Mt, and lead scraps also reached 3.6 Mt. Approximately 40% of lead stocks in China can be used in the future. China's lead market has become saturated in recent years.